2020
DOI: 10.22271/chemi.2020.v8.i3p.9359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of row spacing with different levels of phosphorous and biofertilizer on growth and yield of maize (Zea mays L.)

Abstract: A field experiment was conducted at Crop Research Farm (CRF), SHUATS, Allahabad, during the kharif season of 2017 with 12 treatments replicated thrice in randomized block design, to determine the effect of row spacing with different levels of Phosphorous and biofertilizer on growth and yield of maize (Zea mays L.). This treatment consisted of two treatment of planting geometry 60 cm x 20 cm, 45 cm x 20 cm, three different levels of phosphorous 60 kg/ha, 80 kg/ha and 100 kg/ha. Seed was inoculated and uninocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…[13] Rina et. al., [8] reported that the combination treatment of spacing 60 x 20 cm with 80 kg/ha P on PSB treated seeds obtained the best results with higher results namely in grain yield (5.22 ton/ha), harvest index (43.13%) and test weight (28.33 g). According to these findings it may be considered that offering strategies of spacing and nutrient management techniques like using of biofertilizers may improve the maize production system giving a major emphasis in sustainable agriculture.…”
Section: Sharifi and Namvarmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] Rina et. al., [8] reported that the combination treatment of spacing 60 x 20 cm with 80 kg/ha P on PSB treated seeds obtained the best results with higher results namely in grain yield (5.22 ton/ha), harvest index (43.13%) and test weight (28.33 g). According to these findings it may be considered that offering strategies of spacing and nutrient management techniques like using of biofertilizers may improve the maize production system giving a major emphasis in sustainable agriculture.…”
Section: Sharifi and Namvarmentioning
confidence: 99%
“…al. [8] using a spacing half the size they have experimented, Paul [10] concluded that using spacing distance of 35cm x 10cm gives the maximum production of green fodder. Sharifi and Namvar [11] found that the significantly taller plants, total dry matter was found in intra row spacing of 45cm.…”
Section: Effect Of Spacing On Growth and Yield Of Maizementioning
confidence: 99%
See 1 more Smart Citation